Método tradicional e ativo : uma análise dos estilos de aprendizagem e pensamento crítico de estudantes de farmácia e medicina - Jesus, Elisdete Maria Santos de (2018)
Introduction. The commitment to understand how learning is handled and how students express their thoughts critically has led to the development of theories and methods. Its relevance to teaching can be explained by the evidence that each student has a way of learning and this factor can lead to inadequacies or conflicts between the students' learning styles and the teaching style of the teacher compromising the effectiveness of the process. Objective.To analyze the learning styles and critical thinking of students of Pharmacy and Medicine of the Federal University of Sergipe. Methods. The study was developed in three stages: in the first stage a systematic review of the literature was carried out with the objective of evaluating the relationship between the strategies and teaching methods most appropriate for the learning styles during undergraduate students of Pharmacy courses and Medicine present in the literature; in the second stage a longitudinal study with before-after evaluation was carried out to characterize the preferences of learning styles and critical thinking competence in undergraduate medical students submitted to traditional and active teaching methods; in the third stage a longitudinal study was carried out to analyze the critical thinking skills in Pharmacy students in two courses with different teaching methodologies. Results.The findings of the systematic review indicated that of the 2196 studies analyzed, 20 met the established inclusion criteria. Although it is unclear which learning styles are favored with learning strategies, the Problem Based Learning (PBL) method, audiovisual resources, and research initiation programs have proved to be useful for improving learning experiences. In the longitudinal study, the medical students of the two Campuses presented the same profile of preference of learning styles being characterized by the sensorial, visual, reflexive and sequential styles. With respect to critical thinking, it was found that the students of the active methodology obtained a significant score in the Competence Analysis (p = 0.0323). Overall, students were characterized with high demonstration of critical thinking competence over time. In the study of the analysis of the critical thinking competence, Pharmacy students presented a high demonstration of critical thinking competence. The classification by competence scales showed a significant difference for the Inference (p = 0.0109) scales for the active method and for the Assessment (p = 0.0049), Inference (p = 0.0156) and Explanation (p = 0.0459) for the traditional method. Conclusion. The systematic review revealed that PBL methods, audiovisual resources and computer-aided learning programs have proved useful in improving learning experiences in a number of studies. The students of the medical school even when inserted in different teaching methods had preference for the styles of sensorial, visual, reflexive and sequential learning, being categorized with "high demonstration of competence of critical thinking". For students of the Pharmacy course, it was found that there are differences in the competence of critical thinking when these students are submitted to different teaching methodologies, pointing to a decline in competence Inference to the active and traditional method and improvement of the levels of competence in the scale Assessment and Explanation.